Urinary Incontinence Among Married Women in Turkey: Effects on Quality of Sexual Life and Anxiety - Burcu Korkut, Nergiz Sevinç, Didem Adahan, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Urinary incontinence (UI) is a broad range of public health issues mainly affecting antenatal and postnatal women. However, research about its impacts on women’s psychology and sexuality is inadequate. Aim: The present case-control survey study aimed to compare married women with UI and without UI regarding their quality of sexual life and anxiety levels. Methods and Material: This study was conducted at XXX Public Health Center, Turkey, between September 15, 2021, and December 15, 2021, and included 660 married women aged between 18 and 65 years (median age of 48 years) who were divided into two groups those with UI and those without UI. A questionnaire consisting of a general information form, the Beck Anxiety Inventory (BAI), and the sexual quality of life – female questionnaire (SQOL-F) was administered to all participants. Results: The 330 women with UI (median age, 50 years) were significantly older, had higher education levels, higher income levels, higher employment levels, higher rates of partus, abortus, and curettage, higher rates of chronic diseases, and higher rates of regular drug use (p<0.05 for all). The mean total SQOL-F scores of women with UI were significantly lower than those of 330 women (median age 47.5 years) without UI (37.8 and 66.7, respectively; p<0.001), and total BAI scores of the women with UI were significantly higher than those without UI (27 and 16, respectively; p<0.001). The quality of sexual life was negatively correlated with anxiety levels in women without UI (Spearman’s rho=-0.163, p=0.003) Conclusion: Current analyses revealed the negative impacts of UI on women’s psychology and sexuality. Keywords: urinary incontinence; women; quality of life; anxiety